2010
DOI: 10.1007/s10641-010-9752-4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary niche differentiation of five sympatric species of Platycephalidae

Abstract: The dietary composition and partitioning of food resources between five sympatric species of Platycephalidae inhabiting the coastal waters of New South Wales, Australia was investigated. Samples were collected monthly between March and November 2007 onboard commercial ocean prawn trawlers based in the ports of Yamba and Newcastle. Monthly percentage weight contribution of 12 prey categories was analysed to determine if diet was influenced by the variables: species, location, depth, size and maturity. Of the 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…4), which is consistent with other studies in this marine park [17], [25]. Snapper, P. auratus , was mostly associated with reef, with highest abundance at 25 and 50 m, but also contributed to the halo assemblage at 100 and 200 m (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…4), which is consistent with other studies in this marine park [17], [25]. Snapper, P. auratus , was mostly associated with reef, with highest abundance at 25 and 50 m, but also contributed to the halo assemblage at 100 and 200 m (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the shallow-water preference of small S. flindersi placed them directly in the preferred habitat of S. robusta. It is conceivable that a dietary mechanism ensured the smaller S. flindersi individuals were not competitively disadvantaged , Barnes et al 2011. Alternatively, necessary resources in the shallow strata may not have been limited, reducing the need for species stratification.…”
Section: Population Structuring and Habitat Partitioningmentioning
confidence: 99%
“…Similarities in the ecology of flathead and the species of flatfish infected in this study may promote infection with larvae of S. sagittifer. Notes taken on the dietary items of the flatfish in this study showed a dominance of crustaceans (shrimp and crab claws predominately); flathead are also known to forage on crustaceans(Barnes et al, 2011) and crustaceans are presumed intermediate hosts of various acanthocephalans(Kennedy, 2012).Abdel-Ghaffar et al (2014) found prevalence of infection varied between seasons, with more fish infected, leading to higher prevalence of infection in definitive hosts, over summer months.Previously known from southern Australian waters (and other temperate locations), these are the first records of C. cetaceum from the eastern Queensland coast, albeit from paratenic hosts. The definitive hosts of C. cetaceum include the short-beaked common dolphin, Delphinus delphis (Linnaeus), and the common bottlenose dolphin,…”
mentioning
confidence: 67%